The numbers Three and Twelve give you a product of 36, and a sum of 15
Answer:
Its B
Step-by-step explanation:
Let the number be x.
Therefore, by the problem
x/6-(-3) = 12
or, x/6+3 = 12
or, x/6 = 12-3
or, x/6 = 9
or, x = 9 × 6
or, x = 54
The number is 54.
Step-by-step explanation:
y = ax^n + bx^(n-1) ... + z
(0, 1) tells us that the constant term z = 1.
because x = 0 eliminates all other terms. and as the sum is 1, that means z = 1.
for the other pairs I strongly suspect
(-1, 3) : 2×(-1)² + 1 = 2×1 + 1 = 3
(-2, 9) : 2×(-2)² + 1 = 2×4 + 1 = 9
so, the fitting equation is
y = 2x² + 1